EXPLORING THE RELATIONSHIP BETWEEN TECHNOLOGY ADOPTION, HUMAN CAPITAL, ACCESS TO CREDIT, AND BUSINESS RESILIENCE ON MSME PERFORMANCE IN INDONESIA - D. Iwan Riswandi; Subagyo; Jatmiko Wahyu Nugroho; Iwan Harsono (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study explores the complex relationships that exist between the performance of Micro, Small, and Medium-Sized Enterprises (MSME) in Indonesia and the use of technology, human resource management, credit availability, and business resilience. Partial Least Squares (PLS-SEM), a type of structural equation modeling (SEM), was used to assess a sample of 110 different MSMEs. The results show a complex web of linkages that impact MSME success. These relationships emphasize the critical roles that technology adoption, efficient HRM, enhanced loan availability, and robust business practices play. For policymakers, practitioners, and researchers looking to promote sustainable growth in the Indonesian MSME sector, the report offers insightful information.